Rational Group Counseling with Anxious Underachievers - Sharma, K. L. (Canadian Journal of Counselling and Psychotherapy, 2012)
Although the issue of academic underachievement is of considerable ocial significance, a survey of literature reveals a dearth of effective treatment procedures. The present study was designed to investigate the effectiveness of a rational group approach in the academic recovery of underachievers. Eighty-four anxious high-school underachievers were divided into four equal groups and were exposed to one of the following: rational group counseling, teaching of rational ideas, teaching of study skills, or no treatment. Immediately after the termination of treatments the underachievers receiving rational group counseling showed significantly greater reduction in irrational beliefs and, five months later, they showed significantly greater improvement in school marks.